Answer:
<h2>-5 + 7x</h2>
Step-by-step explanation:
The Commutative Property states that the order of addition or multiplication does not matter.
EXAMPLE 1 : 1 + 2 = 2 + 1 = 3
EXAMPLE 2: 3 x 4 = 4 x 3 = 12
It appears that we cannot use the commutative property on this expression. But we can. First, we need to change - 5 = + -5.
7x - 5 = 7x + -5
Because we now have addition, we can prove the commutative property.
-5 + 7x = 7x + -5
I'm always happy to help :)
What question Would that be
Since the problem is 2x^2-5xy-y^3 we first have to plug in what the x and y stands for, once you do that your problem should look like this:
2(-3)^2- 5(-3)(-2)- (-2)^3
Now take the parentheses away and when you do that your signs change.
2x3^2-5x(-3)x(-2)-(-2)^3
do it again with -5x(-3)x(-2)
2x3^2-30-(-2)^3
now do this with (-2)^3
2x3^2-30-(-8)
Now evaluate the power
3^2 becomes 9
2x9-30-(-8)
then change -(-8) to a positive since two negatives make a positive
2x9-30+8
Now multiply the numbers 2x9
18-30+8
Then do 18-30 which equals -12 then add 8
Now you are left with your answer:
<u>-4</u>
Hope this helps! :3
I am doing this on apex aswell and i am stuck for the last few ones. I know that the answer to #1 is: Natalie- SAS and Emma- SSS the other ones im not so sure about. sorry for the lack of help, just thought one answer is better than none lol
Answer:
The first four terms are;
w(x)= 4 + 2x² - ⁵/₆x⁴+ ¹¹/₃₆x⁶ +......
Step-by-step Explanation:
This is the interpretation of the question
w″ + 3xw′ -w=0
W(0)=4
W′(0)=0
CHECK THE ATTACHMENT FOR STEP BY STEP EXPLANATION